A finite element scheme for the analysis of influence of drainage and grout curtain on seepage under dam foundation - Kabilamany, Kandasamy; Tomiolo, Andrea; Balasubramaniam, A.S.; Ohta, Hideki; Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1982)
This work presents a highly flexible finite element scheme to solve the unconfined seepage problems with special reference to anisotropic nonhomogeneous dams containing complex geometry and material properties. A new finite element scheme has been established to accommodate to the change in position of the free surface after each iteration when solving the overall finite element equations in the above mentioned cases. The proposed scheme has been verified by solving the unconfined seepage problem for a homogeneous isotropic dam and comparing the various field variables such as elevation of the exit point, flows, pore pressures, velocities etc. with the values reported by ISAACS, BAALAH and BOOKER (1980) ; which were obtained by employing six different methods proposed by several researchers. This shows that the scheme presented in this thesis gives the values of the field variables to the required accuracy. The scheme has then been employed to solve a real case of a dam containing a clay core, downstream drainage and a grout curtain. A complete set of computer programs to solve these problems has been developed by the author in APL language. This enables the interaction of the graphical with the numerical outputs in the terminal screen even in the intermediate process of calculations. Hence, errors introduced due to some irregularities can be rectified easily. Extending the scheme established for 2-D case to 3-D, the complete formulation for 3-D seepage with free surface for nonhomogeneous isotropic cases is given by the author. However, coding of the computer program is left to the user.
Thesis (M. Eng.) - Asian Institute of Technology, 1982
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Keywords: Seepage; Dams -- Foundations